Bowhead and Beluga Whale Distributions, Sighting Rates, and Habitat Associations in the Western Beaufort Sea in Summer and Fall 2009–16, with Comparison to 1982–91 - Clarke, Janet T.; Ferguson, Megan C.; Willoughby, Amy L.; Brower, Amelia A. (ARCTIC, 2018)
We analyzed data from line-transect aerial surveys for marine mammals conducted in the western Beaufort Sea (shore to 72˚ N, 140˚–157˚ W) from July to October of 2009–16 to investigate the distribution, behaviors, sighting rates, and habitat use preferences of bowhead and beluga whales. The habitat use data allowed for direct comparison with data collected in the same area from 1982 to 1991. Both species are ice-adapted, migrating through leads in sea ice in spring, and are seasonal inhabitants of the western Beaufort Sea during summer and fall. From 2009 to 2016, bowheads were seen in all survey months, with the highest overall sighting rate (whales per km) in August. Bowhead sighting rates were highest in the whales’ preferred habitats: outer shelf habitat (51–200 m depth) in July and inner shelf-shallow habitat (≤ 20 m depth) in August, September, and October. Beluga whales were also seen in all survey months, with highest overall sighting rate in July. Beluga whales were overwhelmingly associated with continental slope habitat (201–2000 m depth) in all months. Bowhead distribution and depth preferences in summer months of 2009–16 differed from those observed in 1982–91, when bowheads were not seen during limited survey effort in July and preferred outer continental shelf habitat in August. These differences indicate that bowhead whale preference for shallow shelf habitat now occurs earlier in summer than it used to. Beluga distribution and depth preference remained similar between 1982–91 and 2009–16, with strong preference for continental slope during both periods. Differences in sea ice cover habitat association for both species are likely due more to the relative lack of sea ice in recent years compared to the earlier period than to shifts in habitat preference. Habitat partitioning between bowhead and beluga whales in the western Beaufort Sea remained evident except in July, when both species used continental slope habitat. In July – October 2009–16, the distribution, sighting rates, and behavior of both ...